Fuzzy ABC Classification in Inventory Management for a Service Sector Firm - Gündoğar, Emin; Yılmaz, Ayşegül; Erkayman, Burak (Archives of Business Research, 2018)
Companies face with the need for evaluation of inventories in terms of multiple criteria in short time in the varying economic conditions. The ABC Analysis clusters these inventories and produces required reports. However, ABC inventory clustering process has weakness in terms of class distinction. The purpose of this study is obtaining strong optimum results in ABC Analysis by fuzzy clustering of inventories. The case is performed in a firm operating in telecommunications sector.